Triglyceride deposit cardiomyovasculopathy: a rare cardiovascular disorder - Ming Li; Ken-ichi Hirano; Yoshihiko Ikeda; Masahiro Higashi; Chikako Hashimoto; Bo Zhang; Junji Kozawa; Koichiro Sugimura; Hideyuki Miyauchi; Akira Suzuki; Yasuhiro Hara; Atsuko Takagi; et al. (Orphanet Journal of Rare Diseases, 2019)
Abstract Triglyceride deposit cardiomyovasculopathy (TGCV) is a phenotype primarily reported in patients carrying genetic mutations in PNPLA2 encoding adipose triglyceride lipase (ATGL) which releases long chain fatty acid (LCFA) as a major energy source by the intracellular TG hydrolysis. These patients suffered from intractable heart failure requiring cardiac transplantation. Moreover, we identified TGCV patients without PNPLA2 mutations based on pathological and clinical studies. We provided the diagnostic criteria, in which TGCV with and without PNPLA2 mutations were designated as primary TGCV (P-TGCV) and idiopathic TGCV (I-TGCV), respectively. We hereby report clinical profiles of TGCV patients. Between 2014 and 2018, 7 P-TGCV and 18 I-TGCV Japanese patients have been registered in the International Registry. Patients with I-TGCV, of which etiologies and causes are not known yet, suffered from adult-onset severe heart disease, including heart failure and coronary artery disease, associated with a marked reduction in ATGL activity and myocardial washout rate of LCFA tracer, as similar to those with P-TGCV. The present first registry-based study showed that TGCV is an intractable, at least at the moment, and heterogeneous cardiovascular disorder.